ABOUT THE FORM OF THE SOLUTION OF A THIRD-DEGREE EQUATION WITH FUNCTIONAL COEFFICIENTS - Dimov, Lazo (Matematichki Bilten, 2008)
In this work we discuss the following linear differential equation of third degree \(f(x)y’’’ + g(x)y’’ + h(x)y’ + r(x)y = 0,\) and we transform it under certain circumstances in its canonical form (1) whereupon \(a(x)=c,\) which is a differential equation with constant coefficients, and according to the sign of the figuration equations we determine its solution with the formulas (2).